“Then Who Are You?”: Young American Indian and Alaska Native Women Navigating Cultural Connectedness in Dating and Relationships - Katie Schultz; Emma Noyes (Genealogy, 2020)
Despite disproportionately high rates of intimate partner violence among American Indian and Alaska Native (AI/AN) women and associations between adolescent dating violence and partner violence in adulthood, little to no research has focused on dating and relationships among AI/AN adolescents. Using exploratory thematic analysis with focus group data (N = 16), we explore this topic among a sample of young AI/AN women (ages 15–17). Results suggest that dating may enhance or inhibit connections to culture or tribal identity. Moreover, responsibility for sustaining cultural knowledge, practices, and lineage may influence choices of reproductive partners for Native women living within colonial structures of governance. The greatest threat in relationships were similar to those from settler colonialism—loss of culture and consequently, self. Promoting healthy relationships among this population should include cultural safety, identity, and involvement, as well as a focus on broader systems, including enrollment policies, that may influence these relationships. Supportive networks and mentorship related to identity and cultural involvement should be available for young AI/AN women. In response to this Special Issue’s call for work that offers creative approaches to conveying knowledge and disruptions to what are considered acceptable narrative approaches we offer illustrations as well as text.